Improved intrusion accident management using haptic signals in roadway work zone. (February 2022) - Sakhakarmi, Sayan; Park, JeeWoong
Highlights: We introduce a new mechanism of safety perception for intrusion hazards into construction work zones. We modeled tactile message profiles to communicate intrusion-based hazard information. The haptic signals in this mechanism could improve worker hazard awareness about intrusion. Message-encoded haptic signals could help better protect workers from intruding vehicles. Abstract: Introduction: Roadway work zones are known for hazard vulnerability, with many injuries and fatalities each year, due mostly to intrusions. Despite several available measures to improve safety, existing mechanisms are unreliable for workers to perceive alerts, due to the harsh working environment, with loud noise and limited vision. This research attempts to overcome hazard perception difficulties by introducing a new communication mechanism for intrusion hazard perception. Method: The presented communication mechanism is based on past tactile sensing research, and is enhanced by signal profile and message modeling investigations. Experimental field trials were conducted for mechanism evaluation with a goal of improved situational awareness through tactile sensing. Results: The trial results show that users perceive warning messages well, even when their vision and hearing are limited, and that the signalized messages perceived could augment users' understanding of a potential hazard, allowing immediate precautionary actions. Practical Applications : The application of haptic signals in vulnerable work zones has the potential to improve upon limitations in innate sensing (e.g., vision and hearing), thus presenting an opportunity to better protect workers from potential accidents.